Analysis and Design of Employee Attendance System Using QR Code with Webcam (Case Study: PT. Adhicon Perkasa) - Ayuliana, Ayuliana; Nurfitriana, Febrian Vingky; Dirayati, Fadhilah (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
Employee attendance is a process of recording employee attendance that is commonly used in companies, where previously all attendance recording was done manually and on a paper basis, so it took time to recapitulate, and allowed human error to occur. The use of technology in recording attendance, such as fingerprint attendance, web-based attendance, Quick Response Code attendance and others, is expected to help in managing attendance data. The aim of this research is to design a Web and Android-based Quick Response Attendance Code Application that can simplify the process of recording employee attendance and recapitulating daily attendance so that the results obtained are more accurate, then the stored data is used to count employees. need for food money per day. The research method is divided into problem identification, an interview approach is carried out with related parties by taking case studies at PT. Adhicon Perkasa. Solution development is carried out by conducting analysis and system design using uses diagrams and other diagrams. The result of this research is the Quick Response Attendance Code Application which can make the attendance process more accurate, minimize human error, and make it easier to recapitulate attendance for calculating daily meal allowances. It was concluded that with this application it is hoped that employee performance can improve because there is no longer a need to make attendance reports manually and the calculation of meal allowances will become more accurate.